Optimizing water use efficiency in maize (Zea mays L.) production through deficit irrigation in Gazhen-Fuafuat Kebele, Northwest Ethiopia - Melkie, Tadesse; Jemberu, Walle; Bitew, Amare (Frontiers in Agronomy, 2024)
Ethiopia's dominant maize production relies on rain, but growing water scarcity challenges dry season irrigation efforts. This necessitates smarter irrigation techniques to maximize water use efficiency. This study optimizes water use efficiency in maize production through deficit irrigation in Gazhen-Fuafuat kebele, Fogera woreda, Ethiopia. A field experiment was conducted during the 2019/20 dry season, comparing four irrigation levels: 55%, 70%, 85%, and 100% of crop water requirements (ETc). Findings revealed that while higher irrigation levels generally enhanced plant growth and grain yield, irrigation water use efficiency was optimized at 70% ETc. Deficit irrigation at 55% ETc proved to be suboptimal, leading to significant reductions in crop growth and grain production. Conversely, applying 70% ETc resulted in a 30% reduction in irrigation water use without compromising yield. Compared to full irrigation, deficit irrigation at 85% ETc, 70% ETc, and 55% ETc resulted in yield reductions of 8%, 13.5%, and 33.1%, respectively. However, these reductions were accompanied by water savings of 15%, 30%, and 45%, respectively, leading to corresponding increases in water use efficiency of 8%, 23.4%, and 21.9%. These results suggest that deficit irrigation practices can be effectively employed to improve water use efficiency in maize production, especially in the study area facing water scarcity. This study provides valuable insights into the potential of deficit irrigation to improve maize production in Ethiopia while conserving water resources. Therefore, by implementing deficit irrigation strategies and supporting farmers with appropriate training and resources, Ethiopia can enhance its agricultural productivity and ensure food security in the face of increasing water scarcity.